2001
DOI: 10.2176/nmc.41.264
|View full text |Cite
|
Sign up to set email alerts
|

"Early" Apoplexy Due to Traumatic Intracranial Aneurysm. Case Report.

Abstract: A 76-year-old man presented with a traumatic aneurysm of the left internal carotid artery which caused repeated subarachnoid hemorrhages within 20 hours of a fall from a height. Early computed tomography (CT) detected no brain abnormalities, but repeat CT found subarachnoid hemorrhage. Internal carotid angiography detected a pseudoaneurysm, which was not treated because of his poor clinical condition. He died of multiple organ failure. Early detection of a traumatic intracranial aneurysm is important for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…3,5) Review of 171 cases of the TICAs to investigate the location found only two TICAs (1.2%) of the ophthalmic artery. 9) Only five cases of traumatic ophthalmic artery Neurol Med Chir (Tokyo) 52, January, 2012…”
Section: Discussionmentioning
confidence: 99%
“…3,5) Review of 171 cases of the TICAs to investigate the location found only two TICAs (1.2%) of the ophthalmic artery. 9) Only five cases of traumatic ophthalmic artery Neurol Med Chir (Tokyo) 52, January, 2012…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms causing traumatic aneurysms of the supraclinoid ICA are believed to be as follows: Direct injury to the ICA by basal skull fracture, 16,23) overstretching or torsion of the ICA wall by movement of the brain following impact, 21,27) tearing by nearby prominent bony structures, 5,21,25) and avulsion of a perforator. 20,24) Our case was probably caused by basal skull fracture.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8,12,19) Angiography performed the day of injury detected traumatic aneurysms in only 54% of the cases. 16) False negatives accounted for 46% of cases. Therefore, angiography should be performed repeatedly, but less risky modalities such as three-dimensional CT (3D-CT) and magnetic resonance angiography can be selected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations